The linguistic norm and its (in)variants as a basis for the evaluation of lingual expressions - Maras, Tomasz (Acta Universitatis Lodziensis. Folia Germanica, 2015)
The main subject of this article is the linguistic norm and its (in)variants with regard to evaluation of lingual expressions. The article tries to show various German and Polish conceptions of linguistic norms and to point to their reference to lingual errors/mistakes and interference. Functional norm, usus, feel for language and their importance for language standardization are also discussed in the article, together with the relativity of linguistic norm.